Emotional balance as a predictor of speech ethics among junior high school students in Pesawaran - Aprilia Anggraini; Sutiyono Sutiyono; Taridi Taridi (International Journal of Science and Applied Science: Conference Series, 2025)
In the field of education, speaking ethics plays a crucial role as one of the key indicators in assessing the quality of interpersonal interactions. Speaking ethics is not merely about speaking properly; it also involves how an individual conveys thoughts, ideas, opinions, and feelings politely, respectfully, and in accordance with the norms and values prevailing in a particular social and cultural environment. This concept is highly relevant in educational settings, involving not only students and teachers but also all parties engaged in the educational process. In general, speaking ethics reflects moral principles and ethical values that serve as a guide for individuals in communication. These principles are essential for maintaining harmony and comfort in interactions, both within the classroom and in the broader school environment. In this regard, the present study aims to examine the extent to which emotional balance influences ethical speaking behaviour. Emotional balance refers to an individual's ability to manage and regulate emotions wisely across various situations, whether in moments of joy, sadness, anger, or under pressure. This research was conducted in a junior high school  located in the Pesawaran region. The study employed a quantitative approach using survey methods and random sampling techniques. A total of 33 students, all of whom follow the Buddhist religion, were selected as respondents. Data were collected through questionnaires, interviews, and documentation. The data were then analysed using validity and reliability tests, as well as simple linear regression analysis. The results show that emotional balance has a significant and positive effect on ethical speaking behaviour. The better an individual manages their emotions, the more ethically they tend to communicate. However, other factors were also found to have some influence, albeit to a lesser extent.